Evaluating the Impact of Liquidity and Debt Management Strategies on Business Growth and Stability - Ranha, Brithma; Puja, Anjali; Nirmala, Sarita; Asha, Kiran (Scieclouds Publishing, 2023)
This paper explores how firms use assets and liabilities management strategies to enhance business prospects for growth as well as stability. As this was a quantitative study, data was collected from a diversity of firms that were stratified by size and type. An email based close ended structured questionnaire for liquidity management, debt management and investment strategies were used. Altogether, it can be concluded that the best practices in these management strategies demonstrated the largest growth in such factors as revenues and market shares. To examine the relationships between management practices and business outcomes both descriptive and inferential analyses – multiple regression and analysis of variance (ANOVA) – were used. Analyses showed that liquidity management stood out as the significant determinant of business stability; moreover, strategic investment in assets was closely associated with growth. To my knowledge, therefore, this research seeks to fill this explanatory gap by presenting current empirical data on asset and liability management with a view of showing how these management practices impact on organizational performance. These findings imply the need for organizations and firms to enhance strategic financial management can strategies, or mechanisms as tools of survival in competitive marketplaces